ETIOLOGIES OF INFECTIONS IN DIABETIC PATIENTS HOSPITALIZED AT BOUAKE UNIVERTY TEACHING HOSPITAL - Kone, Djakaridja; KONE , Famoussa; YAPO , Martine Tatiana; KADIANE-OUSSOU , Juliette; KONE, Salifou; KARIDIOULA , Jean-Marie; KOUAME , Gille Renaud; ACHO , Jean Kevin; KRA , Ouffoué; OUATTARA , Bourheima (African Journal of Infectious Diseases (AJID), 2023)
Background: Diabetic infections are frequent and the etiologies are multiple. The present study aims to identify the etiologies of the infections of the diabetic patient hospitalized in the University Teaching Hospital of Bouake in Côte d’Ivoire. Materials and Methods: This was a retrospective cross-sectional study conducted in the Internal Medicine Department from January 2019 to December 2020. The study population consisted of hospitalized and infected diabetic patients. Of this study population we included in the study 136 patients. Data analysis was done with Epi Info 7.2.3.1 software. Results: The prevalence of infection in hospitalized diabetics was 75.1%. The mean age of the patients was 52 ± 13.4 years. The sex ratio was 0.7. Diabetes was incidentally discovered in 50% and type 2 diabetes (88.2%) predominated. The reasons for hospitalization were dominated by ketoacidosis (58.1%), glycemic imbalance (19.1%) and hyperosmolar hyperglycemia syndrome (10.3%). Fever was present in 41.2% of cases. The infectious foci were urinary tract infections (29.4%), pneumopathies (28.7%), malaria (21.3%), skin infections (13.2%) and the undetermined focus (7.3%). The infectious focus was unique in 90.4%. The germs identified were plasmodium (21.3%), Escherichia coli (8.8%), staphylococcus (8.3%), yeasts (8.3%) and Enterobacter (6.7%). Beta-lactams (75.6%) were the most prescribed anti-infective treatment. Mortality was 14.7% related to type 1 diabetes (p=0.001), duration of diabetes greater than 5 years (p=0.005), hospitalization latency greater than 7 days (p=0.001), mucocutaneous focus (p=0.005) and Undetermined foci (p=0.001). Conclusion: Diabetic infections are frequent and the etiologies are varied. They must be systematically sought in hospitalized diabetics